Ugly - Napoli, Donna Jo, 1948-; Judge, Lita (New York : Hyperion Paperbacks for Children, 2008)
When all the other birds of Dove Lake turn against him, Ugly's mother has no choice but to protect her family and leave her darling chick behind.
3.3
3-6
Keywords: Ducks -- Juvenile fiction; Swans -- Juvenile fiction; Ducks -- Fiction; Swans -- Fiction; Ducks -- Fiction; Swans -- Fiction